LINGUISTIC-CULTURAL ANALYSIS OF GRATITUDE AND EXCUSE IN ENGLISH AND ITS ITEMS IN UZBEK - Shakirova, Saida (Журнал иностранных языков и лингвистики, 2023)
Our article examines the linguistic-cultural analysis of gratitude and pretense in English and its elements in the Uzbek language.